Respostas
respondido por:
3
x + 2 2 - 1
----------- + ------- = ---
2 x - 2 2 mmc = 2( x - 2)
( x - 2) ( x + 2) + 2 .2 = -1(x - 2)
x² + 2x - 2x - 4 + 4 = -x + 2
x² = - x + 2
x² + x - 2 = 0
a = 1 b 1 c = -2
Delta = b² - 4 . a . c
D = 1² - 4 . 1 . (- 2)
D = 1 + 8
D = 9
- b + ou - VD V é raiz quadrada
x = ---------------------
2 . a
- 1 + ou - V9
x = --------------------
2 .1
-1 + ou - 3
x = -----------------
2
x' = - 1 + 3/2 x" = - 1 -3/2
x' = 2/2 x" = - 4/2
x' = 1 x" = - 2
----------- + ------- = ---
2 x - 2 2 mmc = 2( x - 2)
( x - 2) ( x + 2) + 2 .2 = -1(x - 2)
x² + 2x - 2x - 4 + 4 = -x + 2
x² = - x + 2
x² + x - 2 = 0
a = 1 b 1 c = -2
Delta = b² - 4 . a . c
D = 1² - 4 . 1 . (- 2)
D = 1 + 8
D = 9
- b + ou - VD V é raiz quadrada
x = ---------------------
2 . a
- 1 + ou - V9
x = --------------------
2 .1
-1 + ou - 3
x = -----------------
2
x' = - 1 + 3/2 x" = - 1 -3/2
x' = 2/2 x" = - 4/2
x' = 1 x" = - 2
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás